On Asymptotically Deferred Statistical Equivalence of Sequences - Kosar, Cem; Kucukaslan, Mehmet; Et, Mikail (Univ Nis, Fac Sci Math, 2017)
In this study, combining the definition of asymptotically equivalence of sequences and deferred density, the concepts of asymptotically deferred statistical equivalence and strong deferred asymptotically equivalence of nonnegative sequences are introduced. Besides, the main properties of asymptotically deferred statistical equivalence and strong deferred asymptotically equivalence, some inclusion and equivalence results are given.
Keywords: Asympototically equivalent sequences; statistically equivalent sequences; deferred statistical convergence of sequences